Improving The Quality Of Peer Review: GGA Instructions For Reviewers - Patrick Alexander Wachholz (Brazilian Society of Geriatrics and Gerontology, 2024)
Peer review is an essential and integral part of the editorial and academic publication process that contributes to validate manuscripts submitted to biomedical journals. A good review can greatly improve the quality of published manuscripts, thereby improving the journal's reputation, value, and relevance to the reader. This special article includes the main recommendations of the editorial board of Geriatrics, Gerontology and Aging to its current and future reviewers, aiming at a continuous improvement of quality standards in the peer review process used by the journal. In addition, the importance and types of review processes are discussed, as well as the editorial flow and selection of reviewers, and general and specific recommendations are presented for carrying out good reviews.